Carpal Alignment: A New Method for Assessment - Selles, C. A.; Ras, L.; Walenkamp, M. M. J.; Maas, M.; Goslings, J. C.; Schep, N. W. L. (Journal of Wrist Surgery, 2019)
Background Carpal alignment may be used as a tool to evaluate fracture reduction in patients with distal radius fractures. However, there is little consensus on how to measure and quantify carpal alignment.Purpose The aim of this study was to compare the inter- and intraobserver variability of a new perpendicular method with the existing method in fractured and unfractured wrists. Additionally, the normal distribution of carpal alignment in unfractured wrists was investigated.Patients and Methods Carpal alignment was assessed on lateral plain radiographs using two different methods, one described by Ng and McQueen and another newly proposed method, the perpendicular method. Using the perpendicular method, the observer draws one line along the inner rim of the volar cortex of the radius and one perpendicular line to the center of the capitate. The carpus is aligned when the line along the inner rim transects the center of the capitate. Three examiners measured the carpal alignment in 50 patients with nonfractured and 50 patients with fractured distal radius. Intra- and interobserver variability for both methods were determined.Results The interobserver coefficient for the perpendicular method was 0.98 and that for the Ng method was 0.86. The intraobserver coefficients for three examiners were 0.89, 0.62, and 0.63, respectively, for the Ng method. For the perpendicular method, the intraobserver variability was 0.96, 0.89, and 0.72, respectively. In patients with unfractured wrists, the mean perpendicular to the center of the capitate was 0.25 mm dorsally.Conclusion The new proposed method is a reproducible method for measuring carpal alignment with a high inter- and intraclass coefficient.Clinical Relevance This method of measurement allows for a reproducible technique for measuring carpal alignment.
Keywords: carpal alignment; measurements; distal radius fracture